Gamification in web application for direct selling sales managers / Siti Sarah Othman - Othman, Siti Sarah (2022)
Gamification in Web Application for Direct Selling Sales Managers is a project development, the purpose of the development is to provide assists for company, to help overcome problems and increase the motivation of sales manager. The sales agent and admin also able to use the system, as for sales agent can purchase order in the system and admin can monitor the system so that the system run smoothly. Based on the literature review done, there are two problems are identified. The first problems are company with sales managers has difficulty to manage and keep track of its managers’ sales performance where the performance is based upon the sales made by their subordinates’ sales agents. Next, sales managers have low motivation due to lack of incentives to reward their performance. A set of objectives were identified for the project, which are to identify appropriate gamification elements in an application for sales manager, to develop a web application for sales manager that apply gamification elements and to evaluate and test the functionality of the web application for sales managers. After that, the methodology adopted by the system is the Waterfall Methodology, where only the first three phases are applied, requirements, design, and implementation. All three objectives successfully achieved during the development. The strength of this system will be the effective way to support the sales manager in manage the sales agent, motivate sales manager to increase their sales and makes the sales manager compete with other in a healthy way. There are several system limitations that can be improved in the future.